Route planning algorithms: Planific@ Project - Martín García, Carlos; Martín Ortega, Gonzalo (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
Planific@ is a route planning project for the city of Madrid (Spain). Its main aim is to develop an intelligence system capable of routing people from one place in the city to any other using the public transport. In order to do this, it is necessary to take into account such things as: time, traffic, user preferences, etc. Before beginning to design the project is necessary to make a comprehensive study of the variety of main known route planning algorithms suitable to be used in this project
Keywords: ADL; HTN; JSHOP2; JSHOP2GUI; method; moviliz@; operator; PDDL; planific@; SHOP; STRIPS; IJIMAI